Integration of Shazy equation with constant coefficients - Chichurin, A.V. (Нелінійні коливання, 2003)
The problem of constructing a general solution for the third order Shazy differential equation with six constants parameters is considered. This equation belongs to P-type and is connected with Painleve equations.